THE LANGUAGE OF THE TEXTILE FIELD OF KNOWLEDGE AS AN OBJECT OF LINGUISTIC STUDYING - I. K. Djurayev (Journals Park Publishing, 2022)
This article provides information on engineering terminology and terms belonging to different languages, theoretical problems of terminology. The article on the problem of terms covers various theoretical and practical issues of terminology and terminology. Such issues include the relationship between the term and the world in the common language, the formation, development of terms, their use in periodic stages, synonymous and homonymous terms, determinology in terminology, the existence of reterminolization phenomena, system-structural and functional-semantic analysis of terms.
Keywords: Word formation, affixation, ethno linguistic, lexical knowledge, mental lexicon, , multilingual terminology